REVITALIZING SMALL AND MEDIUM-SIZED CITIES THROUGH ART INTERVENTION: REACTIVATING PUBLIC SPACES (Proceeding of the International Conference on Arts and Humanities, 2024)
By 2050, 70% of the global population will reside in cities, making urban areas central to the future of global life. Currently, large cities have numerous advantages in resident welfare, job opportunities, and public spaces, attracting a large number of young people and ensuring urban vitality. However, this trend has diluted the populations of small and medium-sized cities, causing them to enter an ageing society earlier, and in some cases the risk of disappearing. In order to address this challenge, improving the quality of life of the inhabitants, revitalizing small and medium-sized cities, and rethinking the possibilities of 'activating' urban spaces and branding cities have become important research directions for urban policy makers, designers, and cross-disciplinary collaborations. Artistic interventions are an innovative strategy for the revitalization of small and medium-sized cities and their sustainable social and economic development by enhancing the memory and emotional climate (happiness, sense of belonging, place attachment) of the inhabitants and promoting their cohesion towards the city. This paper analyzes and discusses how artistic interventions can promote innovation and city branding in urban public spaces from both short-term and long-term impact dimensions. Through a simulated practice in the small northern Italian city of Piacenza, the application of the research theory is demonstrated, aiming to provide references and methodologies for sustainable urban regeneration.
Keywords: art intervention; public spaces; city branding; place attachment; urban vitality